PENDEKATAN KETERAMPILAN PROSES DALAM PEMBELJARAN IPA KELAS IV PADA SEKOLAH DASAR NEGERI 02 NANGA BUNUT - Agung, Rosyadi; ., Kaswari; ., Suryani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: In fourth grade elementary school students 02 Nanga Bunut, still experiencing weakness in understanding science learning in particular meteri root, therefore, necessary to do an action or class action research (PTK). This study aims to improve: (1) Motivation student learning, (2) an understanding of teaching materials, (3) the independence of student learning, (4) improve science learning outcomes Elementary School fourth grade students 02 Nanga Bunut. The subject is receiving the action Elementary School fourth grade students 02 Nanga Bunut, the subject is implementing measures that help researchers and implementers are subject science teachers and principals. Data were collected through observation, field notes, review, and documentation. Qualitative descriptive analysis of data with percentages and flow models. Comparison improving student learning outcomes as follows: (1) the percentage of prior studies with an average of 54.33 or 20%, (2) the percentage increase in the first cycle with an average of 61.33, or 60%, (3) The percentage increase in cycle II with an average of 74 of the value of good26.67% and the value was 73.33%. Keywords: Learning outcomes, Process Skills, Learning Science Abstrak : Pada siswa kelas IV SD Negeri 02 Nanga Bunut, masih mengalami kelemahan dalam pemahaman pembelajaran IPA khususnya meteri akar, oleh sebab itu, perlu dilakukan suatu tindakan atau Penelitian Tindakan kelas (PTK). Penelitian ini bertujuan untuk meningkatkan: (1) Keaktifan belajar siswa, (2) pemahaman materi ajar, (3) kemandirian belajar siswa, (4) meningkatkan hasil belajar IPA siswa kelas IV SD Negeri 02 Nanga Bunut. Subjek penerima tindakan adalah siswa kelas IV SD Negeri 02 Nanga Bunut, subjek pelaksana tindakan adalah peneliti dan subyek yang membantu pelaksana adalah guru IPA dan kepala sekolah. Data dikumpulkan melalui observasi, catatan lapangan, review, dan dokumentasi. Analisis data secara deskriptif kualitatif dengan presentase dan model alur perbandingan peningkatan hasil belajar siswa sebagai berikut: (1) persentase sebelum penelitian dengan rata-rata 54,33 atau 20%, (2) persentase meningkat pada siklus I dengan rata-rata 61,33 atau 60%, (3) Persentase meningkat pada siklus II dengan rata-rata 74 dari nilai baik 26,67% dan nilai sedang 73,33%. Kata Kunci : Hasil Belajar, Media Gambar dan Pembelajaran Matematika